1971
DOI: 10.1126/science.171.3977.1268
|View full text |Cite
|
Sign up to set email alerts
|

Skull from Spruce Swamp: Case of Cranial Dysraphism?

Abstract: 219 + 23 and 218-L 20 (1); and 222.4 + 22.4 and 219.6 24.1 (5) based on measurements with two different, commercially available, potassium ion-specific electrodes. To evaluate the applicability of this algebraic extrapolation, I calculated values for Kf1 for each of the measurements made above pH 9 (5, tables 1 and 2 Rather we have made our measurements directly in a region of ionic strength where meaningful activity coefficients may be used. Thus, our method yields thermodynamic rather than conditional values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The majority of the bioarchaeological literature identifies defects located at bregma as congenital herniations/dysraphisms (Gass, ; Ortner, ; Powell, ; Stewart, ; Webb & Thorne, ), although some lesions are more difficult to assess resulting in diagnoses that remain undifferentiated (Blau, ; Sublett & Wray, ). Only six examples of defects at bregma exist in the literature and consistent in each of these papers is the description of the shape, position, and location of the defect (Table ).…”
Section: Bioarchaeological Literature Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the bioarchaeological literature identifies defects located at bregma as congenital herniations/dysraphisms (Gass, ; Ortner, ; Powell, ; Stewart, ; Webb & Thorne, ), although some lesions are more difficult to assess resulting in diagnoses that remain undifferentiated (Blau, ; Sublett & Wray, ). Only six examples of defects at bregma exist in the literature and consistent in each of these papers is the description of the shape, position, and location of the defect (Table ).…”
Section: Bioarchaeological Literature Overviewmentioning
confidence: 99%
“…Powell concluded that the best explanation was trephination, although he did allude to a potential diagnosis of an aperture allowing for herniation of the meninges and brain tissue. Gass (), a neurosurgeon, read Powell's report and noted that the appearance of the anomaly was more consistent with an encepholocele or meningoencepholocele. He describes the condition thusly: “the skull may become ‘saucerized’ also by benign tumors within it and growing out of it, or resting upon it” and that “when this process is present exactly in the midline and an aperture is pierced through the skull at the bottom of the ‘saucer’” one can be confident in a diagnosis of cranial dysraphism (Gass, :1268).…”
Section: Bioarchaeological Literature Overviewmentioning
confidence: 99%
See 3 more Smart Citations